An Analysis of Human Values and Character Building in Indonesia Reflected in Hancock’s The Blind Side Movie - Marcelina Boleng (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2018)
The purpose of the study are; (1) to find out the human values in Hancock’s The Blind Side movie, and (2) To find out which human values in Hancock’s The Blind Side movie reflected to character building in indonesia. The descriptive qualitative design was used in this study to make a clear explanation about human values reflect in this movie. The main isntruments such as script and video file of the movie. And also, flow model method by Miles and Huberman was used in this study to analyze the data. The results of this study were: (1) in the script of this movie reflected there only five kinds of human values aspects reflected in this movie. They are individual values, family values, professional value, moral values and spiritual values. Researcher found that there are four kinds of individual value, eight kinds in family values, one kind of professional value, six kinds of moral values, and one kind of spiritual values. (2) from those five human values aspects, and only five values that refer to character building in Indonesia are honesty, tolerance, hard work, love peace and social care. Meanwhile, character building honesty, tolerance and hard work found in family values. Character building love peace and social care found in moral values